Pengembangan Strategi Peningkatan Kualitas Layanan Publik Di Mal Pelayanan Publik Banyuwangi Menggunakan SERVQUAL Dan IPA - Ramsen Cahyatri Fatmasari; Andung Jati Nugroho (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2025)
The Public Service Mall (Mal Pelayanan Publik/MPP) of Banyuwangi Regency is a public service innovation established in 2017 under the Department of Investment and One-Stop Integrated Services (Dinas Penanaman Modal dan Pelayanan Terpadu Satu Pintu/DPMPTSP). This study aims to evaluate and improve customer service quality at MPP Banyuwangi using the Importance-Performance Analysis (IPA) and Service Quality (SERVQUAL) methods. Enhancing service quality in the public sector is crucial to increasing public satisfaction and trust in government services. The research methodology involves data collection through questionnaires distributed to respondents who use services at MPP Banyuwangi. The service quality dimensions, based on the SERVQUAL and IPA models, are analyzed to identify gaps between customer expectations and perceptions of public services. The results indicate a significant gap between customer expectations and perceptions regarding specific service quality aspects. The implications of these findings suggest that service quality improvements in the public sector at MPP Banyuwangi can be effectively implemented by focusing on the key aspects identified in this study.